MENIMBANG PERBEDAAN RASM Uá¹ MÄ€NÄª: - Mustopa, Mustopa (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
Critics to Indonesian Standard Qur'an concerning the use of rasm continue to be carried out by a number of circles. The book of Difference of Uá¹¡mÄnÄ« Rasm Between Indonesian Standard Qur'an and al-Musá¸¥af al-MadÄ«nah of Saudi Arabia in the Perspective of ad-DÄnÄ« and AbÅ« DawÅ«d by Zainal Arifin Madzkur comes to answer those critics. The review of this book will look at the objectivity of the discussion conducted by the author on the two mushafs that were compared. The tendency of the author of the book is inevitable, but remains in the corridor of scientific objectivity. This book makes a significant contribution, especially to Indonesian Standard Qur'an that has not had a comprehensive scientific foundation yet. The notes are given to the main points of this book in order to give a balanced view, especially relating to the use of the uá¹¡mÄnÄ« rasm in the mushaf. This book shows that the use of the uá¹¡mÄnÄ« rasm in the Qur'an cannot be based only on one or two schools, considering the complexity of the study of the uá¹¡mÄnÄ« rasm. Therefore, the most correct claim cannot be raised as each mushaf has advantages and disadvantages that cannot be avoided.